Penerapan Layanan Informasi Tentang Sex Education melalui Media Boneka pada Anak di TK Islam Bakti II Sobokerto Ngemplak Boyolali - Nurul Ilmi Azizah, Annafi; Rahmawati Putri, Alfiani; Sa’diyah, Chalimatus; Wulandari Kusumastuti, Esty; Nur Hidayah Heristiana, Febria; Ima Farisky, Mufti; Kaamilah Fisabilillah, Nabiilah; Fadillah, Nova; Eka Cahyani, Septiyana (Mulya Literasi Publishing, 2024)
The implementation of sex education for young children is a preventive step to prevent sexual violence, especially amid the increasing cases of child abuse. This community service program was conducted at TK Islam Bakti II Sobokerto, Ngemplak, Boyolali, using educational puppets to introduce which parts of the body can and cannot be touched. This activity involved 23 TK B students and was carried out through the stages of planning, implementation, and evaluation. This activity uses interactive methods such as watching videos, singing, and hands-on practice with educational puppets. This, program also received full support from early childhood education teachers who were involved in every stage of the activities. The results show that this approach successfully improved children's understanding of their body concepts and how to protect them, while creating an enjoyable learning atmosphere. Educational puppet media has proven to be an effective tool in delivering sex education in an age-appropriate and engaging manner. In conclusion, this program has a positive impact on building children's awareness of self-protection, as well as providing a teaching model that can be adopted by other institutions. The sustainability of this program is expected through the development of broader interactive media and teacher training, thereby strengthening preventive efforts against sexual violence in early childhood.